Pesantren-Based Curriculum Management to Enhance the Quality of Learning at Al Azhar 46 Kindergarten, Samarinda - Rika, Fajar Eriza Rikasari; Nurlaili, Nurlaili; Sudarman, Sudarman; Hidayanto, Dwi Nugroho; Gede Mulawarman, Widyatmike; Haryaka, Usfandi (Borneo Educational Journal (Borju), 2025)
Pesantren-based curriculum management is a blend of the national curriculum and the foundation’s curriculum, administered within an educational management system to provide continuous knowledge acquisition in both general sciences and Islamic studies. This study aims to describe the pesantren-based curriculum management, covering planning, organizing, implementation, and evaluation at Al Azhar 46 Kindergarten, Samarinda. The research employs a qualitative descriptive method through a case study approach, utilizing data collection techniques such as observation, interviews, and documentation, with data validity ensured through source triangulation. The findings reveal that: 1) Curriculum planning at Al Azhar 46 Kindergarten begins with an analysis of community needs, emphasizing religious education based on adab (Islamic manners) to instill religious and moral values from an early age. The curriculum is formulated on the philosophical foundation of the Qur’an and Hadith to ensure religious content aligns with Islamic teachings. 2) The pesantren-based curriculum development highlights tahfizh (Qur’an memorization) classes and adab learning, implemented continuously from kindergarten through junior high school to nurture noble character from an early age. 3) Curriculum management implementation at Al Azhar 46 Kindergarten is conducted through structured planning that integrates the national and religious curricula in a balanced manner. The learning process emphasizes teacher role modeling, habituation of religious values, and employs tahfizh methods such as Alsam and Tilawati. 4) The evaluation of pesantren-based curriculum management is carried out regularly and systematically, including annual work meetings, semester coordination meetings, and program evaluations every three months. 5) The implementation of pesantren-based curriculum management at Al Azhar 46 Kindergarten positively impacts the quality of learning. The curriculum management has been executed systematically, adhering to the functions of curriculum management through the development of technical guidelines and integrative modules that facilitate the balanced implementation of both the national and pesantren curricula